The Role of Mammalian Creb3-Like Transcription Factors in Response to Nutrients - Khan, Haris A.; Margulies, Carla E. (Frontiers in Genetics, 2019)
Our ability to overcome the challenges behind metabolic disorders will require a detailed understanding of the regulation of responses to nutrition. The Creb3 transcription factor family appears to have a unique regulatory role that links cellular secretory capacity with development, nutritional state, infection and other stresses. This role in regulating individual secretory capacity genes could place this family of transcription factors at an important regulatory intersection mediating an animal’s responses to nutrients and other environmental challenges. Interestingly, in both humans and mice, individuals with mutations in Creb3L3/CrebH, one of the Creb3 family members, exhibit hypertriglyceridemia thus linking this transcription factor to lipid metabolism. We are beginning to understand how Creb3L3 and related family members are regulated and to dissect the potential redundancy and cross-talk between distinct family members, mediating both healthy and pathological responses to the environment. Here we review the current knowledge on the regulation of Creb3 family transcription factor activity, their target genes and their role in metabolic disease.